2023
DOI: 10.1097/ta.0000000000003955
|View full text |Cite
|
Sign up to set email alerts
|

Prehospital tranexamic acid is associated with a dose-dependent decrease in syndecan-1 after trauma: A secondary analysis of a prospective randomized trial

Abstract: BACKGROUND In the Study of Tranexamic Acid During Air and Ground Prehospital Transport (STAAMP) Trial, prehospital tranexamic acid (TXA) was associated with lower mortality in specific patient subgroups. The underlying mechanisms responsible for a TXA benefit remain incompletely characterized. We hypothesized that TXA may mitigate endothelial injury and sought to assess whether TXA was associated with decreased endothelial or tissue damage markers among all patients enrolled in the STAAMP Trial. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 44 publications
(148 reference statements)
1
5
0
Order By: Relevance
“… 13 18 19 Alternate hypotheses for TXA’s mechanism of action have been explored, particularly as a pro-endothelial therapeutic agent to reduce glycocalyx shedding. 20 Our results add to the existing literature and our TEG findings correspond to the historic TXA mechanism of action.…”
Section: Discussionsupporting
confidence: 87%
“… 13 18 19 Alternate hypotheses for TXA’s mechanism of action have been explored, particularly as a pro-endothelial therapeutic agent to reduce glycocalyx shedding. 20 Our results add to the existing literature and our TEG findings correspond to the historic TXA mechanism of action.…”
Section: Discussionsupporting
confidence: 87%
“…[32][33][34] Multiple adult trauma studies have reported an association between syndecan-1 elevation and poor outcomes. [22][23][24]35,36 Gonzalez Rodriguez et al 22 reported a study of injured adults, defining a cutoff of 40 ng/mL as abnormal and comparing those with higher versus lower levels of syndecan-1; elevated levels were associated with higher injury severity as in this study, as well as mortality and the need for blood product transfusion. In a prospective study of 424 adult subjects, syndecan-1 was an independent predictor of <24-hour, 7-day, and 28-day mortality after controlling for other contributing factors including age, sex, ISS, Glasgow Coma Scale, base excess, platelet count, and hemoglobin.…”
Section: Discussionmentioning
confidence: 57%
“…Adult, in vitro, and animal models have shown a relationship between early TXA adminis-tration and decreased syndecan-1. 35,53,54 There were too few patients to assess the relationship between syndecan-1, TXA, and outcomes in this cohort. A recent multi-institutional study of children with life-threatening hemorrhage showed a relationship between antifibrinolytic medication administration and improved survival but did not include mechanistic data.…”
Section: Discussionmentioning
confidence: 99%
“…It is also hypothesized that adiponectin, produced by adipocytes, may play a restorative role in endothelial function. 26,44,45 Syndecan-1, TM and VEGF have been associated with endothelial cell damage following trauma 26,27,46,47 . Because of the potential relationship between these markers and endothelial function, we categorized these seven markers as endothelial cell damage markers for the purposes of this study.…”
Section: Discussionmentioning
confidence: 99%